THE EFFECT OF QUALITY OF HEALTH SERVICES ON PATIENT SATISFACTION AT THE INTERNAL DISEASE POLYCLINIC OF MEURAXA Hospital BANDA ACEH CITY, 2021 - Ais Izza Rafiqa (Indonesian Journal of Multidisciplinary Science, 2022)
Based on preliminary survey 6 of 20 patients said they satisfied with hospital service, 9 patients were not satisfied because of less comfortable and cramped. 5 patients said the registration department service was quite long. This research used descriptive analytic with a cross-sectional study approach. The population were 2004 patients, the sampling technique used purposive sampling of 95 respondents. Data analysis used univariate, bivariate, and multivariate analyses with logistic regression. The results of the bivariate analysis research showed that the Effective variable has a p-value of .650>.05, and was easily accessible, p-value of .410>.05, while the efficiency of p-value was 0.000>.05, accepted 0.000>.05, impartial 0.000>.05, and safe 0.000>.05. The results of the logistic regression test showed that the safe variable had an OR value of 53.26. It is suggested to Meuraxa Hospital in order improve the quality of health services in the dimensions of efficiency, acceptance, impartiality, and safety which are deemed not good and maintain good quality so that patient health service satisfaction can be achieved optimally.